Details of goods sold to you to-day for shipment to Spain
028-0106-001 DETAILS OF GOODS SOLD TO YOU TO-DAY FOR SHIPMENT TO SPAIN. s.s. 'CARPIO' from London to Valencia 19th January 1937. Goods Quantity Price F.O.B. VALUE FREIGHT RATE Estimated Freight and Insurance C.I.F. VALUE Sugar 275 tons 8/10 cwt (c.i.f. value) £2,429 - - £2,429 Jam 4 tons £25 per ton fob 100 70/- M £28 128 Bacon 4 tons 78/3d cwt " 313 70/- M £33 340 Eggs 50 cases 42/- case " 105 50/- M £19 124 Full Cream Unsweetened Evap. Milk 100 cases 14/4½d case " 72 70/- M £25 97 Full Cream Milk Powder Unsweetened 5 tons £40.15.0d. 204 70/- M £25 229 £3223 £130 £3,353 s.s. PELAYO from Liverpool to Valencia 21st January 1937. Corned Beef 15 tons 160 c/s 24/2s @ 24/6 p. case (fob) 196 40/- W £8 £204 and 440 c/s 48/ls @ 26/6 p.case fob 583 - 22 605 Dried Cod 100 bales 35/40s @ 27/7 bale fob 138 45/- W 12 150 50 " 30/35s @ 28/1 " 70 - 6 76 (Stock are difficult to secure, cannot yet definitely promise even the above quantities) Biscuits 5 tons £52 per ton 260 45/- M 58 318 Mark - C. H. VALENCIA. £1,247 £106 £1,353 GRAND TOTALS £4,470 £236 £4,706 W = weight i.e. Rate per ton weight. M = Measurement i.e. Rate per ton of 40 cubic feet. 292/946/28/106